Evaluación del proceso de maduración y almacenamiento del queso andino madurado - Cevallos Salazar, Steven Humberto (2020)
Evaluating the riped Andean cheese process and storage. Was the Objetive of this research the temperature production and relative humidity monitoring during the two processes was carried out at PROCENCAL cheese factory located in the Pichincha Province, Mejia Canton, Aloasí parish around “ECOFROZ” tocun, the physical, chemical (humidity and pH), microbiological (Staphylococcus aureus and Enterobacteria) and sensory analyses were performed in the Food Analysis and Microbiology Laboratories of CAREN faculty and finally, the analysis of Fat content was performed in the Food Analysis Laboratory at Central University of Ecuador. Initially, four-cheese productions were made with 40 liters of milk per production, thus obtaining four kinds of cheese of different ages, the temperature, and relative humidity was recorded three times per day. Storage was differentiated since cheeses I and III were stored in the environment and cheeses II and IV were stored under refrigeration. Moisture and pH analyze determined that the four kinds of cheese analyzed are within the allowed range, microbiological analyzes determined the importance of the storage medium since cheeses I and III stored under refrigeration obtained favorable results while cheeses II and IV obtained results that exceeded the quality limits of the standard (INEN2607, 2012). Cheeses I and III were subjected to a fat content analysis where they showed that their content was within the parameters, apart from that it could be noted the difference in fat content between a minimally mature cheese before a cheese with more maturity time. Finally, the sensory analysis helped to define that an immature cheese has more acceptability within society, this is attributed to the lack of culture on the ripened cheeses consumption.